(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
The article ponders on federalism in the context of the Brazilian State. To this end, it presents a brief history of the theme in the various subsequent Constitutions. In this analysis, it verifies that the germ of the centralization of powers appears already in the First Republic and, still, configures a framework that the 1988 Constitution seeks to reorder. Next, he approaches the assumptions of federalism, concluding that the economic and social crisis currently being faced stems from the political and institutional crisis. Finally, it demonstrates that addressing these issues involves reviewing the systems of political representation and the distribution of powers.